Motivation as a Mediator of Communication and Work Discipline on Employee Performance : A Study at Karangasem Hospital - Rangga Permana, I Wayan Yogi; Kusumawijaya, Ida Ketut; Sili Antari, Ni Luh (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This research examines the role of communication and discipline in influencing employee performance, with motivation serving as a link, at Karangasem Regional Hospital. In the healthcare sector, the quality of employee performance is crucial for institutional success and is closely tied to effective communication and consistent discipline. The study involved 73 medical personnel using a census approach, with data collected through questionnaires. The analysis included validity, reliability, classical assumption tests, and path analysis. The findings indicate that both communication and discipline positively impact work motivation. This increase in motivation correlates with enhanced employee performance. Furthermore, motivation was found to act as a mediator between communication and work performance, though no similar effect was observed between work discipline and performance. Based on these results, the study recommends that hospital management focus on improving communication patterns among medical staff and strengthen discipline standards to boost motivation and productivity. These findings offer valuable insights for human resource management within the regional health service environment and provide a foundation for future research in similar fields. This research underscores the importance of fostering a motivating work environment through improved communication and discipline to optimize employee performance in healthcare settings. Keywords: Communication, Motivation, Performance, Work Discipline